PERBANDINGAN EFEKTIVITAS PEMBERIAN TERAPI RENDAM KAKI AIR REBUSAN SERAI DAN JAHE TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI DI DESA LAUT DENDANG - Lyran Avril Firdayanti Zega; Hizkianta Sembiring (Indonesian Trust Nursing Journal, 2026)
Hypertension is one of the major health problems among the elderly and is often referred to as a silent killer because it can cause serious complications such as stroke, heart disease, and kidney failure if not properly managed. The objective of this study is to determine the comparison of the effectiveness of lemongrass and ginger decoction foot soaking therapy on reducing blood pressure among elderly patients with hypertension in Laut Dendang Village. A quasi-experimental design with a pre-test and post-test approach was used. Elderly patients with hypertension were divided into two groups: lemongrass and ginger decoction foot soaking therapy. Data were analyzed using the Paired Sample t-Test and the Independent Sample t-Test. The study showed that lemongrass and ginger decoction foot soaking therapies both had an effect on reducing systolic and diastolic blood pressure among elderly patients with hypertension (p value = 0.001 < 0.05). The results of the comparative test indicated that there was a difference in effectiveness between the two therapies, in which ginger decoction foot soaking therapy resulted in a greater reduction in blood pressure compared to lemongrass decoction foot soaking therapy. Ginger decoction foot soaking therapy is more effective as a non-pharmacological therapy in reducing blood pressure among elderly patients with hypertension.